ATTRIBUTES CONSIDERED BY COFFEE CONSUMERS DURING THEIR BUYING DECISION PROCESS: A STUDY USING FACTORIAL ANALYSIS - de Sá, Fabiano Bento; Paiva, Ricardo Viana Carvalho de; Souki, Gustavo Quiroga; Moura, Luiz Rodrigo Cunha (Organizações Rurais & Agroindustriais, 2017)
The aim of this study was to identify, categorize and evaluate the attributes considered by the consumers during their coffee buying decision. A descriptive and quantitative survey with 459 coffee consumers was conducted in Belo Horizonte, MG, Brazil. The results indicate that the attributes considered by the consumers can be grouped into five factors based on importance: (i) Product features - Organoleptic Characteristics, (ii) Brand and Tradition, (iii) Food safety, (iv) Availability and Product Offering, (v) Packaging. The theoretical contributions of this work are the identification of attributes considered by the consumers for buying coffee, the significance verification of these attributes, as well as the separation into factors, which allows a better understanding of the decision-making process of coffee consumers. The contributions of this research for management practices are related to the technical characteristics of the product, food safety, brand, label and packaging management, which are seen as very important factors. Moreover, distribution and trade marketing along the distribution channels are also aspects to be considered. These aspects must be worked out through integrated marketing communication. Finally, the research presents its limitations and several suggestions for future studies.